Modeling the Structural Relationship of Happiness Based on Psychological Well-Being With Self-efficacy Intermediation and Academic Self-regulation in University Students - Iri, Yahya; Fakhri, Mohammad Kazem; Hassanzadeh, Ramazan (International Clinical Neuroscience Journal, 2019)
Background: Happiness is the degree of emotion that a person judges with his overall quality of life as an utterly desirable life. The purpose of this study was to model the structural relationship between happiness based on psychological well-being and self-efficacy and self-regulatory mediation among students at Farhangian University. Methods: This correlation study was carried out using structural equation modeling methods. The statistical population of this study included all undergraduate students at the Farhangian University of Golestan province who were studying in the academic year of 2016-17. By using the Morgan table, 280 people selected through multi-stage random cluster sampling. The data were collected using Savari and Arabzadeh’s educational self-regulatory scale, Sherer Self-efficacy Scale, Oxford Happiness Questionnaire, and Ryff’s psychological well-being questionnaire. Data analysis was performed using path analysis and structural equations with AMOS software. Results: The results showed that psychological well-being had a positive effect on happiness (P < 0.02). Also, the pattern fit results showed that psychological well-being indirectly affects self-efficacy, and self-regulation has an indirect effect on happiness (P < 0.001). Conclusion: The results of this study showed that there is a significant relationship between happiness and psychological well-being with self-efficacy and self-regulation mediation. Therefore, it is possible to raise the level of happiness and psychological well-being of students through the development of programs aimed at promoting self-efficacy and self-regulation of students.